The physical activity of a selected group of Poles during the COVID-19 pandemic - Krzyżanowska, Krystyna (Percepcja turystyki w przestrzeni i w czasie pandemii COVID-19, 2022)
The cognitive goal of the empirical research is to identify motives for undertaking physical activity, the preferences of Polish citizens regarding its forms and the frequency of selected exercises, as well as the effects and limitations on recreational activities during the COVID-19 pandemic. A diagnostic method using a survey technique according to a standardized questionnaire was applied in the study. The research was carried out in 2021 and covered 108 Polish citizens. Among the most important reasons for taking up physical activity, the respondents indicated: improved well-being and stress relief, health and good appearance, a nice figure and pleasure. During the COVID-19 pandemic, i.e. in 2020, respondents’ interest in many forms of physical activity decreased compared to before the pandemic, only the popularity of at-home exercises increased significantly which was probably due to restrictions in access to gyms and fitness clubs. During the pandemic, the number of people who exercised on average three hours or more per week decreased, and the number exercising only an hour or less increased. This is very unfavorable in terms of the physical and mental health of Polish society.